2011
DOI: 10.1088/1468-6996/12/4/045003
|View full text |Cite
|
Sign up to set email alerts
|

Control of the pore architecture in three-dimensional hydroxyapatite-reinforced hydrogel scaffolds

Abstract: Hydrogels (gellan or agarose) reinforced with nanocrystalline carbonated hydroxyapatite (nCHA) were prepared by the GELPOR3D technique. This simple method is characterized by compositional flexibility; it does not require expensive equipment, thermal treatment, or aggressive or toxic solvents, and yields a three-dimensional (3D) network of interconnected pores 300-900 µm in size. In addition, an interconnected porosity is generated, yielding a hierarchical porous architecture from the macro to the molecular sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 71 publications
(83 reference statements)
4
34
0
Order By: Relevance
“…3). Scaffolds 235 fabricated with similar composition and drying method to those 236 used in this work (Román et al, 2011) showed a porosity around 237 95%, with 30% for the pores with the highest diameter, around 65% (Vorndran et al, 2010). The release profiles of Figs.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…3). Scaffolds 235 fabricated with similar composition and drying method to those 236 used in this work (Román et al, 2011) showed a porosity around 237 95%, with 30% for the pores with the highest diameter, around 65% (Vorndran et al, 2010). The release profiles of Figs.…”
mentioning
confidence: 77%
“…In previous work we have described an easy and inexpensive 64 method to obtain agarose/hydroxyapatite scaffolds with hierar-65 chical porosity at room temperature for bone repair application 66 Román et al, 2011). Biocompatibility studies 67 demonstrate that these scaffolds allow the culture of osteoblasts 68 inside and outside the material (Alcaide et al, 2010;Cabañas et al, 69 2014 (Cattalini et al, 2012;83 Coleman et al, 2011;Giger et al, 2013;Nancollas et al, 2006; 84 Rosenqvist et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The aim is that the global properties of the scaffold are supported by both constituents [115,116]. A typical example of a composite is a scaffold prepared by incorporating hydroxyapatite (HA) granules or fibers in a polymeric matrix [117][118][119][120][121][122]. Such studies reveal, how-ever, that the contents of the inorganic and organic phases directly influence the bioactivity and mechanical properties of the scaffolds.…”
Section: Composite Materials and Hybrids For Bone Regenerationmentioning
confidence: 99%
“…Further, it is simple, cost effective and environmental friendly since water is used as solvent. Moreover, water has the advantage of being functioning as a porogen upon freezing [23,24]. Several two component porous scaffold composed of polysaccharide and HAP have been prepared by freeze drying method which include gellan-HAP [25], chitosan-alginate [26], chitosan-HAP [27] and alginate-HAP [28] for bone tissue engineering.…”
mentioning
confidence: 99%